NILAI-NILAI PENDIDIKAN KARAKTER DAN PERSEPSI MASYARAKAT TERHADAP CERITA RAKYAT KERINCI “SAKUNUNG-SAKUNUNG NINAU - Putri Dini Rawati; Nazurty Nazurty; Irma Suryani (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
The purpose of this study was to describe the value of character education and public perceptions of the Kerinci folklore. This research is in the form of qualitative research and uses a descriptive approach. The study used was a sociology of literature study, the data source used was a folklore book entitled Sakunung-Sakunung Ninau originating from Koto Tuo, the indigenous people of Pulau Tengah as well as articles from the internet, journals and other supporting books. Based on the research results, there are values ​​of character education in the folklore of Kerinci Sakunung-Sakunung Ninau. In general, the five aspects of character education values ​​proclaimed by the Ministry of Education and Culture, namely Religious, Nationalist, Independent, Mutual Cooperation and Integrity are contained in the story of the Sakunung-Sakunung Folk. Sakunung Ninau, according to the community's perception, the three respondents said that Sakunung Ninau is a bedtime story filled with advice. It can be concluded that the folklore of Kerinci Sakunung-Sakunung Ninau has character education values, as well as the public's perception that Sakunung Ninau contains advice.